Perancangan Set Furniture untuk Public Space dengan Pemanfaatan Limbah Kayu Jati dan Resin - Claudia Filiana Sunaryo; Grace Mulyono; Frenky Tanaya (Intra, 2019)
Wood is a material favored by people to be used as a furniture’s material, especially teak wood, which causes the demand for teak wood increase. The amount of available teak wood is not enough for the demand. This design aims to design a set of furniture that utilizes teakwood waste in combination with other material to be used in public space. The material used for combination is resin, which are flexible and can increase the value of waste without removing the value of the wood itself. The set of furniture produced is a set of furniture for the hotel lobby consist of bench, stool, coffee table and table lamp using teak wood waste and resin. With the use of teak wood waste, it can prevent the scarcity of teak wood.